Low lysine diet in glutaric aciduria type I - effect on anthropometric and biochemical follow-up parameters - Boy, Nikolas; Haege, Gisela; Heringer-Seifert, Jana; Assmann, Birgit; Hoffmann, Georg F.; Müller, Edith; Burgard, Peter; Kölker, Stefan (Journal of inherited metabolic disease, 2013)
Background: Metabolic treatment in glutaric aciduria type I (GA-I) including a low lysine diet with lysine-free, tryptophan-reduced amino acid supplements (AAS), carnitine supplementation and early start of emergency treatment during putatively threatening episodes of intermittent febrile illness dramatically improves the outcome and thus has been recommended by an international guideline group (Kölker et al, J Inherit Metab Dis 30:5-22, 2007). However, possible affection of linear growth, weight gain and biochemical follow-up monitoring has not been studied systematically.MethodsThirty-three patients (n = 29 asymptomatic, n = 4 dystonic) with GA-I who have been identified by newborn screening in Germany from 1999 to 2009 were followed prospectively during the first six years of life. Dietary treatment protocols, anthropometrical and biochemical parameters were longitudinally evaluated.ResultsMean daily intake as percentage of guideline recommendations was excellent for lysine (asymptomatic patients: 101 %; dystonic patients: 103 %), lysine-free, tryptophan-reduced AAS (108 %; 104 %), energy (106 %; 110 %), and carnitine (92 %; 102 %). Low lysine diet did not affect weight gain (mean SDS 0.05) but mildly impaired linear growth in asymptomatic patients (mean SDS −0.38), while dystonic patients showed significantly reduced weight gain (mean SDS −1.32) and a tendency towards linear growth retardation (mean SDS −1.03). Patients treated in accordance with recent recommendations did not show relevant abnormalities of routine biochemical follow-up parameters.InterpretationLow lysine diet promotes sufficient intake of essential nutrients and anthropometric development in asymptomatic children up to age 6 year, whereas individualized nutritional concepts are required for dystonic patients. Revised recommendations for biochemical monitoring might be required for asymptomatic patients.